Uso de diferentes formulaciones para evaluar el rendimiento productivo de pollos Broiler Cobb 500 en el Cantón Urdaneta - Quiñonez Litardo, Ilda Senobia (2023)
This study addresses the evaluation of the productive performance of Broiler Cobb 500 chickens through the use of different feed formulations. Feed is recognized as playing a critical role in poultry production, affecting costs and bird performance. Broiler chicken farming has expanded throughout the country due to its benefits. The poultry meat market stands out as one of the most important in the world, contributing significantly to global food security and playing a prominent role in the international market. (Sáenz, Food conversion in broiler chicken, 2022) The methodological approach of the study involves the use of experimental observation, with data obtained from various sources such as scientific articles, magazines and books. 200 chickens were used in the research, along with different balanced feed formulations to evaluate their productive performance. A completely randomized design (RCD) was used in the experimental work. The food that was used in treatment T1 was the best food in terms of; (weight gain, feed conversion, carcass yield, no mortality), and the T0 treatment feed, which was the feed that was formulated and made at home, was the best in terms of cost benefit. In treatment T1 and T2, better weight gains were obtained, but this obtained a greater cost and profitability benefit, given that in treatment T0 the weight remained within the average range and this obtained a lower cost benefit. The animals that consumed Balanced T0 food obtained better coloration in their meat. The most consumed food and the one with the least waste was the food from treatment T0.